Synthesis and Characterization of Fe2O3 Nanoparticles Reinforced to Recycled Industrial Aluminium Scrap & Waste Aluminium Beverage Cans for Preparing Metal Matrix Nanocomposites (Fracture and Structural Integrity, 2022)
Increased material demand in all sectors is primarily due to exponential growth in population to fulfill human needs and comforts. Recycling of collected aluminium beverage cans and Al 6061 alloy scraps from industries ensures energy savings with reduced environmental problems in fabricating composite parts economically. The iron oxide (α-Fe2O3) nanoparticles were prepared by precipitation method using ferric chloride and ammonia as a precursor. The prepared nanoparticles were characterized by using Transmission Electron Microscope (TEM), X-Ray Diffraction (XRD) and Fourier Transform Infrared (FTIR). Stir cast processing route ensures uniform mix of reinforcement nanoparticles in matrix material. The prepared nanocomposites (matrix: Al Scrap (90% Scrap Al 6061 alloy + 10% Waste Al can); reinforcement: 2%, 4% and 6% wt. of Al matrix) were mechanically characterized for hardness and tensile strengths. It was observed that, increased percent of Fe2O3 nanoparticles in the metal matrix nanocomposite (MMCs) resulted in significant increase in hardness and tensile strength values. Fractography analysis examined viz. scanning electron microscope (SEM) revealed a ductile failure for as-cast Al scrap followed by brittle failure in Al MMC's.
Keywords: Aluminium metal matrix nanocomposites; Ferric oxide nanoparticles; TEM; XRD; FTIR; SEM